LA EVALUACIÓN EDUCATIVA EN FUNCIÓN DE LA MEJORA DEL PROCESO PEDAGÓGICO - Betsabé Mairi Bauza Barreda; Maribel Fernández Noguel (University of Las Tunas, 2018)
Este artículo se dirige a presentar ideas esenciales sobre la fundamentación de la función de mejora sobre la base de la evaluación educativa desde la perspectiva de comprenderlos y utilizarlos en virtud del proceso pedagógico. Integra los fundamentos teóricos a través de los componentes orientador y procedimental que otorga una posición dinamizadora a las direcciones principales del trabajo educacional, como soporte para la comprensión y profundización de los resultados evaluativos alcanzados por el Sistema Nacional de Educación, destaca la orientación de las acciones educativas con el propósito de perfeccionar el proceso pedagógico, lo que muestra la posibilidad de utilizar las formas, vías y métodos de organización para la introducción de los resultados de las investigaciones pedagógicas. ABSTRACT This article is the result of the work done in the research project associated Branch Program "Evaluation of the Quality of Education" in Las Tunas; which has among its priority lines the development of methodological proposals for the care and education of the results of Cuban students who have participated in different national and international evaluation studies. Hence, the merits of the enhancement function based on educational evaluation from the perspective of understanding and use under educational process. The proposal integrates the theoretical foundations through guidance and procedural components that gives higher structure and revitalizing the Main Directions of Educational Works, as support for deepening understanding and assessment results achieved by the national education system and as for targeting educational activities to improve the educational process, which shows the possibility of using the forms, ways and methods of organization for the introduction of the results of educational research. The assessment of the appropriateness of the methodology consists of stages and actions that are reflected in educational practice, judging by the sources. KEY WORDS: improve function, guiding components, main directions.